Development of FRC Materials with Recycled Glass Fibers Recovered from Industrial GFRP-Acrylic Waste - Kishan Patel; Rishi Gupta; Mohit Garg; Boyu Wang; Urmil Dave (Advances in Materials Science and Engineering)
Fiber-reinforced concrete (FRC) and engineered cementitious composite materials have demonstrated promising requisite in construction industry owing to its superior mechanical and durability properties. In this study, a sustainable approach was taken, i.e., to use industry waste as a reinforcement with improved interfacial bonding leading to enhanced mechanical performance of FRC. An efficient in situ recycling process allowed the authors to extract glass fibers from glass fiber-reinforced polymer acrylic waste. Concrete mixes with low fiber dosages including 0.1%, 0.2%, and 0.3% (by volume) of recycled as well as virgin glass fibers were prepared. The slump of concrete was maintained ∼150 mm by using high water-reducing admixture (HWRA). Notably, lower amount of HWRA was required for raw glass fibers vis-à-vis recycled ones due to its hydrophobic nature. Overall, FRC enclosing 0.3% recycled glass fiber demonstrated >20% enhancement in compressive, split tensile, and flexural strength as compared to control (after 28 days of curing), also supported by morphological analysis.